'He makes a fool out of you': The shift in social structure in The Cage. Issue 1 (9th August 2012) - Lloyd, Matt
While adopting a theme and story that are common in short fiction film-making – a child's encounter with suffering and mortality – The Cage nonetheless confounds narrative expectation. Adrian Sitaru challenges short film conventions through his choice of character focus and naturalistic style, expressing subtle shifts in family dynamics.